Ergothioneine Protects Against UV-Induced Oxidative Stress Through the PI3K/AKT/Nrf2 Signaling Pathway - Li Y; Gao J; Liu S; Chen S; Wei X; Guan Y; Li X; Li Y; Huang Z; Li G; Zhao Y; Liu P; et al. (Dove Medical Press, 2024)
Yongchao Li,1,* Jinfeng Gao,2,* Shuhua Liu,1 Shijian Chen,3 Xiaoyue Wei,3 Yalun Guan,1 Xuejiao Li,1 Yunfeng Li,1 Zhongqiang Huang,1 Ge Li,1 Yuhong Zhao,3 Pinghua Liu,4 Yu Zhang1 1Guangdong Provincial Key Laboratory of Laboratory Animals, Guangdong Laboratory Animals Monitoring Institute, Guangzhou, 510663, People's Republic of China; 2Guangdong Quality Supervision and Testing Station for Medical and Health Care Appliances, Institute of Biological and Medical Engineering, Guangdong Academy of Sciences, Guangzhou, 510632, People's Republic of China; 3School of Pharmacy, Guangdong Pharmaceutical University, Guangzhou, 510006, People's Republic of China; 4Department of Chemistry, Boston University, Boston, MA, 02215, USA*These authors contributed equally to this workCorrespondence: Yu Zhang; Pinghua Liu, Email zhangyugzh@hotmail.com; pinghua@bu.eduBackground: Ergothioneine (EGT) is an antioxidant, which could be detected in human tissues, and human skin cells could utilize EGT and play an anti-oxidative role in keratinocytes. And in this study we are going to elucidate whether EGT could protect the skin from photoaging by Ultraviolet (UV) exposure in mice and its molecule pathway.Methods: Histological analysis was performed for evaluating the skin structure change. Malondialdehyde (MDA) and superoxide dismutase (SOD) levels were measured with biological assay for evaluating oxidative and antioxidative ability of skin exposed to UV light. And the level of marker molecules in mouse skin were detected by hydroxyproline (Hyp) assay, immunohistochemical analysis, Western blot, and quantitative real-time PCR (qRT-PCR). The markers of skin aging and cell death were tested by cell culture and treatment, Western blot and qRT-PCR.Results: EGT decreased the levels of inflammatory factors induced by UV exposure in mouse skin. MDA and SOD activity detection showed that EGT decreased MDA levels, increased SOD activity, and upregulated PI3K/Akt/Nrf2 signals in mouse skin exposed to UV, which further activated Nrf2 in the nucleus and enhanced the expression of Nrf2 target genes. In the cell model, we revealed that EGT could inhibit the increase in senescence-associated β-galactosidase-positive cells and p16 and γ-H2A.X positive cells induced by etoposide and activate PI3K/Akt/Nrf2 signaling. Moreover, a PI3K inhibitor blocked EGT protection against etoposide-induced cell death.Conclusion: The study showed EGT may play an important protective role against cell damage or death through the PI3K/Akt/Nrf2 signaling pathway in skin.Keywords: ergothioneine, skin aging, PI3K/Akt, Nrf2